Ruang Lingkup dan Dasar Hukum Pelayanan Publik - Sri Yulianti Mozin; Nia Rahmadani Bangko; Ni Ketut Juliawati (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study examines the scope and legal basis of public services in Indonesia, focusing on the implementation of Law No. 25 of 2009 on Public Services. The research employs a normative juridical method with qualitative analysis. Findings indicate that despite the existence of comprehensive legal frameworks, challenges persist in the effective delivery of public services, including issues related to transparency, accountability, and adherence to service standards. The study underscores the necessity for continuous legal and institutional reforms to enhance public service quality.